Development Of Sultan Abu Bakar Spillway Dam Rating Curves For Flood Mitigation Strategies - Kamarulzaman, Fasihah (Universiti Sains Malaysia, 2018)
Dam has multiple functions, it is not only built for power generation but also as flood mitigation purposes. However, the discharge off the dam has to be managed properly so that it can act as the final line of defence in order to mitigate the flood impact to downstream areas. The main objective of this study is to develop discharge rating curve for tilting gate, radial gates and the combination of both gates through a hydraulic physical model of Sultan Abu Bakar Dam, Cameron Highland, Pahang. The hydraulic physical model of Sultan Abu Bakar Dam was produced as a non-distorted model scale of 1/25. Equipment was utilized during the testing process was Nixon Streamflo Velocity Meter and Ultrasonic Flow Meter. Nixon Streamflo Velocity Meter is used to measure the velocity of water at the opening of the gate while Ultrasonic Flow Meter used to measure the overall discharge of the piping system during the physical simulation of the model. In order to ensure the accuracy of the testing equipment, a calibration process of this equipment was conducted using a hydraulic flume experimental in the Hydraulics Laboratory, PPKA. The result from the calibration processes showed the relationship of discharge (l/s) with the upstream head (mm) of reservoir at different opening of the gate. For the full scale hydraulic physical model, opening of three radial gates and a full opening of tilting gate gave the highest discharge which is 214.5m³/s. This constructed mono-chart of gates discharge released helps TNB in decision process of gate opening in order to mitigate the downstream flooding due to unscheduled water released from the SAB Dam.